Comparative Study of Pleurotus ostreatus Mushroom Grown on Modified PAN Nanofiber Mats - Sabantina, Lilia; Kinzel, Franziska; Hauser, Thomas; Többer, Astrid; Klöcker, Michaela; Döpke, Christoph; Böttjer, Robin; Wehlage, Daria; Rattenholl, Anke; Ehrmann, Andrea (Nanomaterials)
Pleurotus ostreatus is a well-known edible mushroom species which shows fast growth. The fungus can be used for medical, nutritional, filter, or packaging purposes. In this study, cultivation experiments were carried out with Pleurotus ostreatus growing on polyacrylonitrile (PAN) nanofiber mats in the presence of saccharose and Lutrol F68. The aim of this study was to find out whether modified PAN nanofiber mats are well suited for the growth of fungal mycelium, to increase growth rates and to affect mycelium fiber morphologies. Our results show that Pleurotus ostreatus mycelium grows on nanofiber mats in different morphologies, depending on the specific substrate, and can be used to produce a composite from fungal mycelium and nanofiber mats for biomedical and biotechnological applications.